Tindak Pidana Homoseksual Dalam Putusan MK Nomor 46/Puu-Xiv/2016: Perspektif Hukum Pidana Islam - Yuhasnibar Syah; Lastrina Lastrina (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2022)
Abstract: Constitutional Decision Number 46/PUU-XIV/2016 raises various views. The decision rejected a request for an expansion of Article 292 of the Criminal Code on homosexuals. Regarding this problem, what are the provisions of Decision No. 46/PUU-XIV/2016 regarding homosexual crimes, how and the considerations of the Constitutional Court judges in deciding homosexual criminal cases in Decision Number 46/PUU-XIV/2016, and how Islamic criminal law regarding homosexual crimes in the Constitutional Court Decision Number 46/ PUU-XIV/2016. This research is analyzed by means of descriptive-analysis. The result of the research is that the provisions of homosexual crime in Article 292 of the Criminal Code regulates same-sex sexual abuse, or obscenity in the category of homosexuals. The Constitutional Court Decision Number 46/PUU-XIV/2016 in principle contains a request to expand the scope of Article 292 from previously only adults with children to adults with adults. There are three reasons and also the considerations of the judges of the Constitutional Court in deciding cases of homosexual crimes in Decision Number 46/PUU-XIV/2016, namely juridical considerations regarding the criminal policy or criminal policy, juridical considerations on the application of the principles of legality and consideration of the substance of the petition. Article 292 of the Criminal Code against Article 1 paragraph (3), Article 28D paragraph (1), and Article 28G paragraph (1) of the 1945 Constitution. From the perspective of Islamic criminal law, the Constitutional Court's decision is not in harmony, or at least has not been able to apply legal aspects criminal law based on religious norms and moral norms.Abstrak: Putusan Mahkamah Konstitusi Nomor 46/PUU-XIV/2016 memunculkan ragam pandangan. Putusan tersebut menolak permohonan pemohon salah satunya tentang perluasan Pasal 292 KUHP tentang homoseksual. Terhadap masalah tersebut, bagaimana ketentuan Putusan No. 46/PUU-XIV/2016 tentang tindak pidana homoseksual, bagaimana alasan dan pertimbangan hakim MK dalam memutus perkara tindak pidana homoseksual dalam Putusan Nomor 46/PUU-XIV/2016, serta bagaimana tinjauan hukum pidana Islam tentang tindak pidana homoseksual dalam Putusan MK Nomor 46/PUU-XIV/2016. Penelitian ini analisis dengan cara deskriptif-analisis. Hasil penelitian bahwa ketentuan tindak pidana homoseksual dalam Pasal 292 KUHP mengatur tentang pencabulan sesama jenis, atau pencabulan kategori homoseksual. Putusan MK Nomor 46/PUU-XIV/2016 pada prinsipnya berisi permohonan untuk memperluas cakupan Pasal 292 dari sebelumnya hanya orang dewasa dengan anak-anak menjadi orang dewasa dengan orang dewasa. Terdapat tiga alasan dan juga pertimbangan hakim Mahkamah Konstitusi dalam memutus perkara tindak pidana homoseks dalam Putusan Nomor 46/PUU-XIV/2016, yaitu pertimbangan yuridis terhadap kebijakan kejahatan pidana atau criminal policy, pertimbangan yuridis terhadap penerapan asas-asas legalitas dan pertimbangan substansi permohonan atas Pasal 292 KUHP terhadap Pasal 1 ayat (3), Pasal 28D ayat (1), dan Pasal 28G ayat (1) UUD 1945. Dilihat dari kaca mata hukum pidana Islam, putusan MK tidak selaras, atau sekurang- kurangnya belum mampu menerapkan aspek hukum pidana yang didasari norma hukum agama dan norma susila.